European standards of business planning as part of integrated development of housing and communal services of the region (Economics and region, 2018)
The problems of housing and communal services, which lead to poor financial condition of the enterprises of this branch are presented. The necessity of business planning, including European standards, both for the enterprise managers, as well as for public authorities is justified. It is proved that properly developed business plan is part of the integrated development of housing and communal services of the region.
Keywords: housing and communal services; the financial condition; business plan; European standards